2005
DOI: 10.1002/ajhb.20404
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the genome ancestry of individuals classified as White in the State of Rio Grande do Sul, Brazil

Abstract: One hundred nineteen individuals classified as White, living in different localities of the Brazilian state of Rio Grande do Sul, were studied in relation to the HVS-I region of the mitochondrial DNA (mtDNA). The male fraction of the sample (N = 74) was also tested for seven Y-chromosome polymorphisms. In a specific population (Veranópolis), a city characterized by a large influence of the Italian immigration of the 19th century, the results from the maternal and paternal sides indicated almost complete Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
53
1
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 27 publications
12
53
1
10
Order By: Relevance
“…In our study, the admixture estimate for the White sample was 0.89 ± 0.01 European, 0.06 ± 0.01 African and 0.05 ± 0.01 Amerindian. As shown in Table 2, the high European component is similar to that found in the Brazilian Y-chromosome study carried out by Carvalho-Silva et al (2001) and in the study by Marrero et al (2005) who investigated a population sample from the southernmost Brazilian state of Rio Grande do Sul which has a predominantly White population, but greater than that verified with HLA polymorphisms (Probst et al, 2000). Ethnic admixture based on five Y-STR loci in the present study showed a high predominance of the European component in the White and Mulatto samples.…”
supporting
confidence: 58%
“…In our study, the admixture estimate for the White sample was 0.89 ± 0.01 European, 0.06 ± 0.01 African and 0.05 ± 0.01 Amerindian. As shown in Table 2, the high European component is similar to that found in the Brazilian Y-chromosome study carried out by Carvalho-Silva et al (2001) and in the study by Marrero et al (2005) who investigated a population sample from the southernmost Brazilian state of Rio Grande do Sul which has a predominantly White population, but greater than that verified with HLA polymorphisms (Probst et al, 2000). Ethnic admixture based on five Y-STR loci in the present study showed a high predominance of the European component in the White and Mulatto samples.…”
supporting
confidence: 58%
“…However, the patients' color distribution was the same as the one found by Parra et al, who analyzed skin color and genomic ancestry in Brazilians and found an European dominance in the south of Brazil (27). Germans and Italians are the main immigrant groups in Rio Grande do Sul, a southern Brazilian state (28). According to the last demographic census, 87.5% of the state population was classified as white, 5% as black, 7% as brown, 0.1% as Asian, and 0.4% as Amerindian; whereas in Brazil, 53.7% are white, 6.2% are black, 38.4% are brown, 0.4% are Asian, and 0.4% are Amerindians (IBGE Census 2000; http:// ibge.gov.br).…”
Section: Discussionmentioning
confidence: 66%
“…We used only a Caucasian sample from Rio Grande do Sul. Genetic studies by Marrero et al (39) using seven γ-chromosome polymorphisms comparing 5 subjects classified as white from Veranópolis, a city with a large Italian descendant community, and other samples from different localities of Rio Grande do Sul showed differences in ethnic contribution. In the Veranópolis sample, almost all subjects presented European ancestry.…”
Section: Discussionmentioning
confidence: 99%